The Swedish father/non-birthing parent visit: evaluating implementation fidelity among child health nurses one year after voluntary implementation - Rahel-Ochido Ibilola Odonde; Olov Aronson; Michael B. Wells (BMC, 2022)
Abstract Swedish child health centres (CHCs) have created a series of visits for fathers/non-birthing parents. The primary aim was to assess child health nurses' implementation fidelity of the father/non-birthing parent visits, with a secondary aim of exploring predictor variables for fidelity. In 2017, nurses voluntarily implemented a series of father/non-birthing parent visits in Region Stockholm. Nurses (n = 122) completed baseline and 8-12 month follow-up surveys. Multiple imputation was used for missing data. Register data on the number of fathers attending the three-to-five month visit was used. Frequencies of nurses reporting good overall adherence to the home visit, three-to-five week visit, and three-to-five month visit were 86%, 76%, and 68%, respectively. A total of 3,609 fathers attended the three-to-five month visit in 2018, where over half of the visits were at 14 of the 134 CHCs. Multiple linear regression showed that working for a private CHC, seeing more fathers, and nurses' perceptions of receiving enough support predicted higher three-to-five month visit adherence. After nurses saw eight fathers, they were more likely to adhere to the guidelines.